1/3 magnetization plateau and frustrated ferrimagnetism in a sodium iron phosphite - Vasiliev, A. N.; Volkova, O. S.; Zvereva, E. A.; Ovchenkov, E. A.; Munaò, I.; Clark, L.; Lightfoot, P.; Vavilova, E. L.; Kamusella, S.; Klauss, H.-H.; Werner, Johannes; Koo, Changhyun; et al. (Physical review, 2016)
The sodium iron phosphite NaFe3(HPO3)2(H2PO3)6 is studied by ac-magnetic susceptibility, pulsed-field magnetization, specific heat, and high-frequency electron spin resonance (HF-ESR) measurements combined with Mössbauer spectroscopy and density-functional calculations. We show that this compound develops ferrimagnetic order below TC=9.5K and reveals a magnetization plateau at 1/3 saturation. The plateau extends to Bc∼8T, whereas above Bc the magnetization increases linearly until reaching saturation at Bs∼27T. The Mössbauer spectroscopy reveals two magnetically nonequivalent iron sites with the 2:1 ratio. The HF-ESR spectra are consistent with a two-sublattice ferrimagnet and additionally pinpoint weak magnetic anisotropy as well as short-range spin order that persists well above TC. The ferrimagnetic order in the title compound is stabilized by a network of purely antiferromagnetic exchange interactions. The spin lattice comprises layers coinciding with the crystallographic (10-1) planes, with stronger couplings Ji∼1.5K within the layers and weaker couplings Ji=0.3−0.4K between the layers. Both intralayer and interlayer couplings are frustrated. The ensuing ferrimagnetic order arises from a subtle interplay of the frustrated but nonequivalent exchange couplings.
Gesehen am 04.06.2020